TRIALS AND TRIBULATIONS: THE STORY OF THE SAFER 2 STUDY. Issue 5 (18th April 2015) - Chatters, Robin; Snooks, Helen; Gaze, Sarah; Koniotou, Marina
Abstract : Background: The SAFER 2 study is an RCT looking to improve the care provided by ambulance service to elderly patients who fall, by providing paramedics with a complex intervention consisting of a paramedic training programme, referral pathway to Falls Prevention Services, clinical support, a clinical decision flowchart and referral feedback. The study received confirmation of funding in December 2008; originally, patient recruitment was scheduled to finish in December 2011. Methods: Information regarding the progress of the study was sought from study staff, study timelines and quarterly reports sent to the study funders (HTA). General information regarding study progress, as well as events that caused unforeseen set-backs to the study timetable were extracted from these sources and the "story" of the study written in chronological order. Results: Progress was delayed by a decision by the NIGB to reject an application to access patient's records without consent; we therefore required written consent from patients that would be particularly difficult to obtain. Following ethical approval in February 2010 (11 months behind schedule), the study team worked to confirm participating sites—two falls services within Nottingham had to decline participation, as well as a Health Board within Wales. In early 2010 participating services were confirmed, allowing R&D approvals to be gained for 26 participating trusts. Patient recruitment started in early 2011. Due to issues with patient throughput and retrieval of patient demographics to assess eligibility, a funded extension was granted by the HTA in order to extend recruitment until June 2012. Discussion: Evaluation of the study was delayed due to issues with ethical approval, site participation and patient eligibility screening and recruitment. Other studies, in other areas of research, have had similar issues, including the COnStRUCT and Family Links studies, which were set-back due to issues with NHS R&D approvals and attribution of costs.